Comparative Study of Hydrodynamic Performance of Submerged Water Jet Propeller and Conventional Propeller Under Multiple Operating Conditions - Jiayi Li; Lei Ma; Dongyang Chen; Yunpeng Qi; Tiechao Bai; Guang Pan (Machines)
As global shipping accelerates toward a green and low-carbon transformation, submerged water jet propulsion has emerged as a promising alternative to traditional propellers due to its high speed efficiency, noise reduction, and adaptability. This study establishes a high-fidelity CFD (computational fluid dynamics) model incorporating vehicle body wake characteristics, validated through open-water experiments. A comparative analysis reveals that the vehicle body wake improves propulsion efficiency by 4.66% for conventional propellers and 2.32% for submerged water jet systems in near-surface operations while exacerbating cavitation-induced efficiency losses by 1.7% and 1.0%, respectively. Notably, submerged water jet propulsion demonstrates superior performance under high-velocity conditions, achieving 5–12.27% higher efficiency than conventional propellers across both open-water and vehicle body wake-affected scenarios. These findings substantiate submerged water jet propulsion’s advantages in complex flow fields, offering critical insights for marine propulsion system optimization.